A Didactic Proposal to Develop Critical Thinking in Mathematics: The Case of Tomás - Lina Fonseca; Sónia Arezes (European Teacher Education Network, 2017)
Critical thinking is an essential skill that schools should develop in every student at every level. As it is a complex and difficult task to accomplish, it should be introduced early on in a child's education, and continue to be developed. With this in mind, a study was conducted to analyse the way in which grade 6 students solved maths problems to see which aspects of critical thinking were used and developed. A qualitative case study was design. Although the study was carried out within a short time frame, it was possible to detect characteristic aspects of critical thinking used by students, which shows that there is a need for more research to be done